Perancangan Sistem Monitoring Kualitas Air Menggunakan Arduino Berbasis Internet of Things - Cicih Sri Asih Daevi; Kecitaan Harefa (CV. Multi Kreasi Media, 2022)
Water is one of the most important natural resources and is widely used by humans. If the water quality decreases, the benefits of the water itself will also decrease. Then water quality needs to be maintained, one of which is by controlling water quality. Water quality control can be done by monitoring water conditions (monitoring). Monitoring of water quality in south quartert still uses ph litmus paper so that it can only know the ph level when checking. So it is necessary to have a tool that makes it easy to monitor water, one of which is using Arduino Uno. The use of this arduino also uses IoT (Internet of Things) through the Bylink application. It is hoped that the Arduino system design can facilitate the engineering team in monitoring the water in South Quarter.